If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4ln(x + -4) = 4 Reorder the terms: 4ln(-4 + x) = 4 (-4 * 4ln + x * 4ln) = 4 (-16ln + 4lnx) = 4 Solving -16ln + 4lnx = 4 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -4 + -16ln + 4lnx = 4 + -4 Combine like terms: 4 + -4 = 0 -4 + -16ln + 4lnx = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-1 + -4ln + lnx) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-1 + -4ln + lnx)' equal to zero and attempt to solve: Simplifying -1 + -4ln + lnx = 0 Solving -1 + -4ln + lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '1' to each side of the equation. -1 + -4ln + 1 + lnx = 0 + 1 Reorder the terms: -1 + 1 + -4ln + lnx = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -4ln + lnx = 0 + 1 -4ln + lnx = 0 + 1 Combine like terms: 0 + 1 = 1 -4ln + lnx = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (p+3)x^2+(2p+3)x+p+5=0 | | -.4x-9=.9 | | 5x+14=-28x-9x | | 19-3e=2-5(e+1) | | (y^2+2)(4y+7)= | | 2r^2+3r-20=0 | | (3y-3)(y+3)= | | 5x-3=2+6x | | 7=2r+5r | | -129=-3(8-7p) | | (y+9)(y+6)= | | 5x+1=14x-73 | | 6d-2(d-2)=3(d-12) | | (x+7)(2x^2-6x-2)= | | 5b-3=7b+11 | | 4x+10y=35 | | x(5-x)+4(x^1)= | | (5x-6)(4x-7)= | | (5x-7)(3x-2)= | | -7=12-k | | 4d-3=21 | | -32=x-17 | | 237x^2-56x= | | 8x^5y(9x^2+x^2y^3-8y^4)= | | 5a+13=7e-21 | | 3x^2-19x=63 | | 7y-5y=6 | | (4x-5)+(3x-1)= | | (4x^6)(-2x^5)(3x^9)= | | 24.2-18.5P=6.6P-1.9(9P+2) | | 12=k-2+6k | | (-x^2+3x)+(2x^2+7)+(5x-2)= |